Analisis Kebutuhan dan Distribusi Guru di Indonesia: Kajian Pustaka tentang Perencanaan Jumlah dan Kualitas Tenaga Pendidik - Siti Sainah; Sutrisno; Fetti Kennisah Putri; Muazza; Aprillitzavivayarti (Program Studi Manajemen Pendidikan, 2025)
This study aims to analyze teacher needs, quantity planning, quality, and distribution in Indonesia through a qualitative literature study approach. Data were obtained from various scientific sources such as journals, policy reports, and official documents from the Ministry of Education, Culture, Research, and Technology. The analysis shows that teacher needs in Indonesia are not yet aligned with available positions, exacerbated by a wave of mass retirements that has increased the deficit in several regions. Teacher number planning faces major obstacles in the form of inaccurate data and weak coordination between agencies, resulting in recruitment not always reflecting actual needs in schools. In terms of quality, competency improvement programs such as certification and training have not consistently improved pedagogical performance, particularly in areas with limited access. Furthermore, teacher distribution remains unequal, with a concentration in urban areas and shortages in Frontier, Remote, and Disadvantaged areas. These findings emphasize that the issues of teacher quantity, quality, and distribution are interrelated and require an integrative policy approach. Consequently, the government needs to develop an integrated education data system, strengthen needs-based planning, and implement incentives and ongoing professional development programs to encourage equitable teacher distribution across Indonesia.